Avaliação da ansiedade de depressão na gravidez - Silva, Mônica Maria De Jesus (2014)
Pregnancy is a period of intense change in women's lives, which can directly reflect on their mental health. What causes are observed increases in symptomatology or even the development of psychiatric disorders during the prenatal period, including anxiety and depression, which can lead to severe maternal/fetal consequences. The present study aimed to assess the presence of anxiety and depression in pregnant women. This is an epidemiological, descriptive-analytical study, cross-sectional and quantitative approach. The sample consisted of 209 pregnant women who received prenatal care units in five Primary Health Care within the Health System, managed by the Municipal Health Secretary of a municipality in the southern state of Minas Gerais, which corresponded to a prevalence of 50%, 95% confidence and a margin of error of 5%. For data collection, which took place from January 16 to March 7, 2013, we used the Hospital Anxiety and Depression Scale for assessment of mood disorders and a tool for characterizing pregnant containing socioeconomic and demographic variables, current pregnancy history and past, lifestyle and pre-existing disease, striking events of life and interpersonal relationships. For descriptive and analytical statistical analyzes of the data using SPSS software, version 17.0 was used. Chi- square, Fisher exact, Shapiro-Wilk test and Mann-Whitney tests were performed and also calculated the average rank and the odds ratio (odds ratio). Variables that were significantly associated with anxiety and depression were included in the logistic regression model. The study was approved by the Ethics Committee in Research of the Federal University of Alfenas opinion under 113.129. As a result it was found that 26,8% (56) of the women had prenatal anxiety and 14,8% (31), depression. It was evident that the occupation, history of abortion/threatened premature labor, presence of complications in previous pregnancies, maternal desire in relation to pregnancy, the number of abortions, the number of cigarettes smoked per day and the use of drugs are associated with the occurrence of anxiety in pregnancy and depression in this period was associated rankings on the number of pregnancies, family support, the number of births, number of children, number of cigarettes smoked per day, beverage consumption alcohol, use of daily medications, history of mental disorder, the presence of winds striking the last 12 months and history of domestic violence. This study showed that the idea of ​​pregnancy is a period of total well -being for all women is wrong and that there is a need to implement actions to prevent mental disorders in this period through screening and monitoring of mental health throughout the prenatal care, for better prenatal care and reducing adverse health of the mother and fetus obstetric outcomes.